2009
DOI: 10.1152/japplphysiol.00122.2008
|View full text |Cite
|
Sign up to set email alerts
|

Repeated-bout exercise in the heat in young athletes: physiological strain and perceptual responses

Abstract: A short recovery period between same-day competitions is common practice in organized youth sports. We hypothesized that young athletes will experience an increase in physiological strain and perceptual discomfort during a second identical exercise bout in the heat, with 1 h (21°C) between bouts, even with ample hydration. Twenty-four athletes (6 boys and 6 girls: 12-13 yr old, 47.7 Ϯ 8.3 kg; 6 boys and 6 girls: 16 -17 yr old, 61.0 Ϯ 8.6 kg) completed two 80-min intermittent exercise bouts (treadmill 60%, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 57 publications
1
27
0
4
Order By: Relevance
“…7,17,18 Importantly, the schedule should be altered to reasonably optimize safety. For example, to minimize acute overload and undue fatigue, an appropriate schedule that allows for adequate recovery between games or practices should be strongly considered.…”
Section: Recommendationsmentioning
confidence: 99%
“…7,17,18 Importantly, the schedule should be altered to reasonably optimize safety. For example, to minimize acute overload and undue fatigue, an appropriate schedule that allows for adequate recovery between games or practices should be strongly considered.…”
Section: Recommendationsmentioning
confidence: 99%
“…10,11 All may be compromised at modest levels of hypohydration (approximately 2%). 5,9 However, extreme deviations on either end of the physiological range (hypohydration or hyperhydration) can compromise health and organ function.…”
mentioning
confidence: 99%
“…The study on thermoregulation and tolerance of exercise-induced heat in children by Bergeron [14] is relevant in this respect, since it is imaginable that children may use their mobile phone shortly after exercise. Bergeron showed that young adults have similar cardiovascular and thermoregulatory capacities as adults and that training, intensity of the exercise and environmental conditions are the relevant parameters in the body's thermal and physiological response [14].…”
Section: Applicabilitymentioning
confidence: 99%
“…Bergeron showed that young adults have similar cardiovascular and thermoregulatory capacities as adults and that training, intensity of the exercise and environmental conditions are the relevant parameters in the body's thermal and physiological response [14]. It will be extremely difficult to translate the added absorption of a local and small amount of energy due to a mobile phone call or due to a nearby base station into an additional increase of the body temperature or estimate an acceptable time-temperature threshold for these circumstances.…”
Section: Applicabilitymentioning
confidence: 99%